Product Demand Forecasting Using Artificial Neural Network (ANN) - Zainal Abidin, Zulhanim (Universiti Sains Malaysia, 2005)
This thesis is to forecast the product demand using Artificial Neural Networks (ANN). This thesis helps readers to understand Artificial Neural Network (ANN). Question about what is ANN, how ANN work and how to used ANN to predict and simulate the data to forecast the product demand can be found in this thesis. General use of ANN in other fields also include in this thesis. This thesis also includes the literature review from many journals by researchers in forecasting which proves that ANN is really suitable for forecasting because of its accuracy. By using the Neural Network Toolbox in the Math lab, Feedforward Back propagation Neural Network is chosen for forecast and simulates the data to complete this project. The data used for training ANN are is the actual data from the production line. After the training, the forecast data compared well with the actual data.